Anxiety, Uncertainty, and Resilience During the Pandemic Period Anthropological and Psychological Perspectives - Gabrielli, Fabio; Irtelli, Floriana (IntechOpen, 2021)
The COVID-19 pandemic has had adverse effects on many people's mental and physical health. As such, this book explores research, theories, biopsychosocial perspectives, and intercultural studies about the pandemic with the ultimate goal to promote better quality of life, resilience, and psychological wellbeing of the general population during this period.